2016
DOI: 10.1039/c6ra11249h
|View full text |Cite
|
Sign up to set email alerts
|

Surface patterned hydrogel film as a flexible scaffold for 2D and 3D cell co-culture

Abstract: Herein we report a facile route for the preparation of surface patterned dynamic hydrogel films, which are not only a matrix to encapsulate one type of cell in 3D but also a substrate to support aligned aggregates of magnetic silica rods to adhere another type of cell in 2D. This enables the composite hydrogel films to be flexible scaffolds for engineering multi-cellular tissues.Chemical cues and topography of a scaffold are able to affect cell behaviour and hence the quality of tissue regeneration. 1-4 For ex… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
10
0

Year Published

2016
2016
2023
2023

Publication Types

Select...
7

Relationship

3
4

Authors

Journals

citations
Cited by 18 publications
(10 citation statements)
references
References 38 publications
0
10
0
Order By: Relevance
“…The dynamic hydrogel is also useful as an extracellular matrix (ECM) to encapsulate cells for 3D cultures and even for 2D/3D co‐cultures . Moreover, the ECM is also injectable, which minimizes surgical injury during operations.…”
Section: Benzoic‐imine‐based Hydrogelsmentioning
confidence: 99%
See 1 more Smart Citation
“…The dynamic hydrogel is also useful as an extracellular matrix (ECM) to encapsulate cells for 3D cultures and even for 2D/3D co‐cultures . Moreover, the ECM is also injectable, which minimizes surgical injury during operations.…”
Section: Benzoic‐imine‐based Hydrogelsmentioning
confidence: 99%
“…[121] The dynamic hydrogel is also usefula sa ne xtracellular matrix (ECM) to encapsulate cells for 3D cultures and even for 2D/3D co-cultures. [122][123][124][125] Moreover,t he ECM is also injectable, which minimizes surgical injury during operations. For exam-ple, it has been shown that the viabilityo fH eLa cells was not affectedb yi njectioni naGC/OHCÀPEGÀCHO mixture through a2 1-gauge needle and subsequent 3D proliferation was observed in the as-formed hydrogel.…”
Section: Applications In Drug Delivery and Tissue Engineeringmentioning
confidence: 99%
“…Poly(ethylene oxide) (PEO; MW = 2 kDa), glycol chitosan (GC, MW ∼ 250 kDa), and sodium alginate (MW ∼ 150 kDa, M/G ratio ∼ 1.6) were purchased from Sigma-Aldrich (St. Louis, United States). Benzaldehyde-capped poly(ethylene oxide) (CHO-PEO-CHO) and silica nanoparticles (average diameter of 12 nm) were synthesized according to our previous reports ( Ding et al, 2010 ; Zhu et al, 2016 , 2017 ). BG particles were synthesized according to our previous work ( Ji et al, 2017 ).…”
Section: Methodsmentioning
confidence: 99%
“…[ 296 ] Similarly, RGD‐functionalized magnetic silica rods were also used to produce aligned patterns onto a composite hydrogel, promoting precise orientation of the encapsulated cells. [ 297 ] Nonetheless, the use of magnetic forces to pattern hydrogels has been less common due to the need for synthetic modifications required to add a magnetic responsive moiety to the desired patterning molecule.…”
Section: Fabrication Of Patterns Through Non‐contact Forcesmentioning
confidence: 99%